The Relationship between Patient Safety Culture and Adverse Events among Nurses in Tehran Teaching Hospitals in 2019 - Edris Kakemam; Mohammadreza Sheikhy-Chaman (Hamadan University of Medical Sciences, 2020)
Introduction: Patient safety culture has been identified as one of the important factors in reducing hospital adverse events and improving patient safety. The present study was conducted to investigate the relationship between patient safety culture and adverse events among nurses of selected teaching hospitals in Tehran. Methods: This cross-sectional study was performed in 2019 on 260 nurses in 7 hospitals affiliated to Tehran University of Medical Sciences. Data was collected using the patient safety culture questionnaire and the frequency of adverse events. Multiple logistic regression was used to investigate the relationship between patient safety culture and adverse events in SPSS 22. Results: Among the dimensions of patient safety culture, the highest mean score was related to the dimension of "organizational learning" and the lowest score was in the area of "information exchange and transmission". Between 35.4% and 51.9% of nurses estimated that they had experienced one of six adverse events in the past year. Logistic regression results indicated that dimensions of management support for patient safety, general understanding of patient safety culture, teamwork within organizational units, communication and feedback about errors, staffing issues and information exchange and transmission were significant predictors for adverse events (P<0/05). Conclusion: The results of the present study confirmed the hypothesis that improving the patient safety culture leads to decrease in the incidence of adverse events among nurses, therefore promoting the safety culture in hospitals of country should be considered as one of the main priorities of management programs.